Justice is in the eyes of the beholder: Eye tracking evidence on balancing normative concerns in torts cases - Christoph Engel; Rima Maria Rahal (Max Planck Institute for Research on Collective Goods, 2020)
Frequently deciding legal cases requires an assessment in multiple, conceptually incompatible dimensions. Often one normative concern would call for one decision, and another normative concern for a different decision. The decision-maker must engage in balancing, with no help from overarching normative theory. A typical situation is torts. The decision must regularly balance concerns on behalf of the victim, the tort feasor and society at large, both on utilitarian and deontological grounds. In this paper we use eye tracking to investigate in which ways laypersons' thought processes react to normative conflict in a set of 16 torts vignettes. If normative conflict is present, participants are less likely to agree with the likely outcome if the case were tried in a German court; they take longer to decide, and they fixate longer on normative concerns presented on a decision screen. Eye movements show that participants indeed consider multiple normative concerns in competition.
hdl:21.11116/0000-0005-8E7E-F
Keywords: D01; D81; D91; K13; K40; 330; torts; fundamental normative relativity; compensation; deterrence; utilitarianand deontological concerns; balancing; eye tracking; machine learning